STRATEGI GURU DALAM MENGATASI KONFLIK ANTAR SISWA MELALUI PENDEKATAN MANAJEMEN KONFLIK INTERPERSONAL DI SD NEGERI 3 LAKATAN - Puspitasari Amrin, Adelia; Ummah BK, Muh Khaerul; Mustakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe teachers’ strategies in managing student conflicts through an interpersonal conflict management approach and to identify the challenges and obstacles teachers face in its implementation at SD Negeri 3 Lakatan. This research employed a qualitative descriptive method. The subjects were fifth-grade teachers, while the object of the study was the strategies used by teachers to manage interpersonal conflicts among students. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that teachers applied various interpersonal conflict management strategies, including collaborative, accommodating, compromising, competing, and avoiding approaches. The collaborative strategy was the most dominant and effective, as it fostered empathy, mutual respect, and fairness among students. These strategies not only helped resolve conflicts but also instilled important character values such as honesty, responsibility, and discipline. The main challenge faced by teachers was encouraging students to be honest and open, while external obstacles included unsupportive social environments, limited parental involvement, and time constraints.Therefore, the success of teachers’ strategies in managing student conflicts can be optimized through synergy between schools, families, and the community. This study is expected to serve as a reference for teachers and future researchers in developing effective conflict management strategies in elementary school settings.